2020
DOI: 10.1029/2019jb019325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Decadal Kinematic Characteristics of the Daguangbao Landslide Using Multiplatform Time Series InSAR Observations After the Wenchuan Earthquake

Abstract: The Daguangbao landslide was the largest landslide triggered by the "5.12" Wenchuan Mw 7.9 earthquake. This landslide is among the few superlarge-scale landslides of 1 billion m 3 magnitude worldwide. As the landslide accumulation represents a potential hazard, long-term monitoring and geological interpretation of the Daguangbao landslide is important to reveal the postsliding deformation characteristics and laws of this landslide type. To study the kinematic characteristics 10 years postearthquake, the landsl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Suppose in the study area, N SAR images were shot at the N times t 0 , t 1 , ⋯, t N-1 , respectively, and M ( ) interference image pairs are generated. The differential interference phase of the k th differential interferogram in Pixel ( x , y ) is generated from the SAR images shot at the times t a and t b ( t a < t b ) and is calculated in Equation (1) [ 70 , 72 , 73 ]. in which and are the differential interference phases at the times t a and t b , respectively; and are the displacements in the SAR line of sight (LOS) at the times t a and t b , respectively, which is relative to the displacement at the initial time t 0 ; , , and are the phases of topography, atmosphere, and noise, respectively; and represents the sensor wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Suppose in the study area, N SAR images were shot at the N times t 0 , t 1 , ⋯, t N-1 , respectively, and M ( ) interference image pairs are generated. The differential interference phase of the k th differential interferogram in Pixel ( x , y ) is generated from the SAR images shot at the times t a and t b ( t a < t b ) and is calculated in Equation (1) [ 70 , 72 , 73 ]. in which and are the differential interference phases at the times t a and t b , respectively; and are the displacements in the SAR line of sight (LOS) at the times t a and t b , respectively, which is relative to the displacement at the initial time t 0 ; , , and are the phases of topography, atmosphere, and noise, respectively; and represents the sensor wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…SBAS processing can be used to obtain displacement time series, and it has been applied to monitor the deformation trends of geologic hazards such as earthquakes (Liu et al 2021;Jafari et al 2023), volcanoes (Doke et al 2021;Festa et al 2022), and landslides (Luo et al 2020;Khan et al 2023). The basic principle is to consider the deformation value as the product of the deformation rate and the time span (Berardino et al 2002;Lanari et al 2004).…”
Section: Sbas Processingmentioning
confidence: 99%
“…The detailed information of the used Sentinel-1 images is presented in Table S2 and the spatial coverage of SLCs and the geometric relationship between the SLCs and the study area are shown in Figure S1. It is noteworthy that the combination of ascending and descending data can reduce the slope effects on the observed geometry [57]. The STRMGL1 digital elevation model with a resolution of 30 m was downloaded from the Land Processes Distributed Active Archive Center (https://lpdaac.usgs.gov (accessed on 12 October 2023)) and used for co-registration and flat-earth phase removal in the single interferogram generation processes of SLCs.…”
Section: Data Setsmentioning
confidence: 99%
“…In addition, the combination of both ascending and descending orbit data sets can overcome the poor observation induced by the shadow and foreshortening effects of SAR images to increase the detection ratio of potential landslides and, therefore, improve the identification of potential landslides. Therefore, the combination of multisensor data with different paths would also be helpful for observations in all azimuths [57]. For landslide detection with InSAR techniques in alpine forest regions, some key points need to be stressed in future studies.…”
Section: Future Landslide Identification Using Insar Techniquesmentioning
confidence: 99%